IFLA Agenda of Green and Sustainable Library: a Literature Study - Narendra, Albertoes Pramoekti (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2023)
Green library sustainability initiatives include all the wise decisions that must be made to maintain the balance between the library system and the underlying environmental system. The green library philosophy advocates a careful understanding of the environment and the creation of methods for managing library facilities and programs while keeping environmental concerns in mind. This study aims to build the understanding and perception of librarians about the concept of green libraries for environmental sustainability; and analyze the practices adopted by libraries according to the IFLA checklists in libraries in several locations. This research method uses literature search in the Library, Information Science & Technology Abstracts database. A search was conducted on the google scholar, focusing on documents published between 2010 and 2020 using the search terms “green libraries” “sustainable/sustainable/eco-friendly” “IFLA checklist” revealing 22 results. The title of each reference returned is checked for relevance and appropriateness. The results show that the concept of green and sustainable logistics has received increasing attention and consideration from the government sector, academia, practitioners, and international organizations. The result of a systematic investigation that combines conference proceedings, reports, and valuable books in the field of green libraries and is expected to illustrate a more comprehensive knowledge map for future research on Green and Sustainable Libraries.